GTAW WELDING REPAIR QUALITY ANALYSIS ON SPARGER HEADER WITH LIQUID PENETRANT AND LEAK TEST - Devina Hermawati; Moh Fawaid (Department of Mechanical Engineering Education, 2026)
Damage to sparger headers, such as material thinning and leakage, can reduce system reliability and disrupt industrial operations. Repair welding using Gas Tungsten Arc Welding (GTAW) is commonly applied; however, its quality must be verified to ensure safe reuse. This study evaluates the quality of GTAW-based repair welding on a corrosion-damaged sparger header using Non-Destructive Testing (NDT), namely Liquid Penetrant Testing (LPT) for surface defect detection and leak testing for sealing performance under pressurized conditions. Unlike previous studies that focus on newly fabricated welds under laboratory conditions, this study evaluates repair welding performance on an actual industrial component affected by corrosion-induced wall thinning. The combination of surface inspection using LPT and functional validation through leak testing under real operating conditions provides a more comprehensive assessment of repair quality. Results show no surface indications in LPT and no leakage during testing at 1.2 kg/cm² for 37 minutes. These findings indicate that the repaired weld meets acceptance criteria and is suitable for reuse. The results provide a reliable basis for assessing repair welding quality in industrial components.